Research progress of spontaneous intracerebral hemorrhage: overseas reports from Chinese scholars - Chao PAN; Zhou-ping TANG (Chinese Journal of Contemporary Neurology and Neurosurgery, 2018)
Spontaneous intracerebral hemorrhage (ICH) is a global public health concern with high mortality and poor functional outcomes. In recent years, some breakthroughs were made in researches on pathophysiology, neuroprotection, prevention and treatment, prognosis and risk of rehemorrhage of ICH. Some research achievements from Chinese scholars have gained attention and recognition around the world. In this paper, advances in ICH research on pathophysiology, neuroprotection, prevention and treatment, prognosis and risk of rehemorrhage will be overviewed based on high?quality overseas papers from Chinese scholars published in recent 5 years.